Cold-water immersion does not accelerate performance recovery after 10-km street run: Randomized controlled clinical trial - Dantas, G.; Barros, A.; Silva, B.; Belém, L.; Ferreira, V.; Fonseca, A.; Castro, P.; Santos, T.; Lemos, T.; Hérickson, W. (Research Quarterly for Exercise and Sport, 2020)
The use of strategies to assure better post-effort recovery is frequent in sports settings. There are several interventions available for exercise induced muscle damage recovery, but cold-water immersion (CWI) stands out among them. The effects of CWI are unclear in the literature and, although the number of street runners has been growing, there is a gap in the scientific evidence regarding the use of CWI to recover runners` performance after a 10-km street run. Purpose: The goal of our study was to analyze the effects of CWI on the recovery of muscle damage markers after a 10-km street run. Method: We randomly assigned thirty male recreational street runners, immediately after a 10-km street run, into three recovery groups: control (rest for 10 minutes), immersion (10 min immersed in water without ice at room temperature) and CWI (10 min immersed in water with ice at 10ºC). We assessed pain, triple hop distance, extensor peak torque and blood creatine kinase levels pre- and post-run, post-intervention and 24 hours after the run. Results: The 10-km run was enough to decrease triple hop distance and extensor peak torque, and increase levels of creatine kinase (p < 0.05); however, we found no time/group interactions in any of the assessed variables after we applied the appropriate interventions (p > 0.05). Conclusion: 10-min CWI at 10°C was no more effective than water immersion and rest in recovering muscle damage markers after 10-km runs.